PENGARUH FREKUENSI PEMBERIAN VITAMIN E TERHADAP POST PARTUS ESTRUS DAN POST PARTUS MATING SAPI PERANAKAN FRIESIEN HOLSTEIN - Sunardi, Sunardi; Nugroho, Dimas; Daryatmo, Joko (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This study aimed to determine the effect of the frequency of vitamin E application on the reproductive performance of postpartum FH crossbreed cows, which Include Post Partus Estrous (first estrus after calving) and Post Partus Mating (first mating after calving). The study used treatment giving vitamin E to cows after calving with treatment 0 (P0)/control, treatment 1 (P1) was injected on the 7th and 14th days after calving and treatment 2 (P2) was injected on the 7th day, the 14th day after calving and 17th day after calving. Post Partus Estrous (PPE) and Post Partus Mating (PPM) were the treatment variables observed. Giving vitamin E on the 7th, 14th, and 17th days after calving (P2) showed a very significant effect (P<0.01) on Post Partum Estrous (PPE). The results of ANOVA analysis of treatment 2 (P2) days 7, 14, and 17 after calving showed a very significant effect (P<0.01) on Post Partus Mating (PPM). This study shows that the P2 treatment with vitamin E injection on days 7, 14, and 17 after calving obtained the best reproductive performance by producing the shortest Post-Partus Estrus (PPE) of 51 days and the shortest Post-Partus Mating (PPM) of 71.83 days.